Unearthing the burden of melioidosis in North India – an emerging threat in a non-endemic region - Shweta Raina; Disha Gautam; Rohit Kumar; Kavita Sisodia; Chiranjay Mukhopadhyay; Harpreet Kaur; Mohammed Ashiq; Rushika Saksena (Current Research in Microbial Sciences)
Burkholderia pseudomallei (B. pseudomallei) is the causative agent of the high-mortality disease called melioidosis. It is a severe infection that can be misdiagnosed due to variable presentation and low awareness among clinicians of the disease. It is endemic in India and well-described in southern and eastern coastal states. In the last decade, sporadic cases of melioidosis have been diagnosed in North Indian states, predominantly Rajasthan and Gujarat. The reported cases highlight the many risk factors for infection in this region that was not previously recognised as being endemic for melioidosis, including high prevalence of diabetes mellitus, alcoholism, and large rural population engaged in paddy cultivation. Climate change results in frequent flooding and waterlogging in urban areas, leading to exposure of soil harbouring B. pseudomallei, thus a contributing factor to the rise in cases in cities. As North India has not previously been considered an endemic region for melioidosis, wider awareness amongst clinicians and laboratorians is essential for early identification of symptoms, testing for B. pseudomallei in microbiology laboratories, and timely management of the disease to save lives lost to misdiagnosis. The present article describes various aspects of melioidosis in North India including diverse clinical manifestations, risk factors, and possible reasons for misdiagnosis and underreporting.